Kajian terhadap Tingkat Kerusakan Pahat pada Pembubutan dengan Metode Minimum Quantity Lubrication (MQL) - Rika Dwi Hidayatul Qoryah; Allen Luviandy; Mahros Darsin (Diponegoro University, 2020)
This study aims to observe the tool deterioration following application of minimum quantity lubrication method (MQL). The designed MQL system is completed with an Arduino controller system which was able to be either manually-controlled or automatically-controlled. The tool used in this study is DCMT 11 insert type. The Taguchi method using the Orthogonal Array L9 design was used to compile the design of experiments with variations in depth of cut, coolant composition, and cooling fluid application methods. Each variable consists of three levels. Tool deterioration evaluated by observing it under an optic microscope from three sides of the tool. There are four levels of tool deterioration. The value of tool deterioration of each tool is the accumulation of each side view. ANOVA analysis found that depth of cut, cutting tool composition and method of applying coolant influence tool deterioration in percentage by 32.69%, 17.30 % and 12.82% respectively. Moreover, the minimum tool deterioration would be achieved when using the parameter combination of depth of cut of 1.6 mm; mixture composition of 3:7; and using the temperature-controlled MQL.